KRITIK HIERARKI KEBUTUHAN MASLOW BERDASARKAN PRINSIP CINTA KASIH DALAM PERJANJIAN BARU - Welly Welliam Polly; Hartati Muljani Notoprodjo; Kezia Tesalonika Hutauruk (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2022)
Maslow's Hierarchy of Needs theory is widely used in many fields because it intuitively seems logical. The purpose of this research is to evaluate this theory - its grouping of needs, hierarchy, and the way to get to self-actualization - by using biblical anthropology and principle of love derived from the New Testament by using biblical theological approach. The result shows that the theory has three fundamental errors so that it should not be used as a way for humans to actualize themselves. First, the exclusion of God, the Creator and the perfect Source of Eternal Love so it does not include the need for understanding self-identity and meaning/purpose of human existence to achieve self-actualization and not seek the fulfillment of love from God. Second, the placement of the need for love is not in the primary needs along with physical needs. Third, the separation of the needs of self-esteem and belonging from the needs of love and placed above or after the needs of love while these two needs are automatically met when the needs of love are satisfied. Since man is made up of spirit and body, and spirit is more important than body, love and physical need are primary needs that when satisfied will enable man to achieve his/her should-be self-actualization, without needing to go through the levels of needs for self-esteem and belonging.